Cuban revolution in America : Havana and the making of a United States Left, 1968-1992 - Latner, Teishan (Justice, power, and politics., 2018)
When a popular revolution prevailed on America's doorstep in 1959, it provoked the wrath of the American political establishment but fueled intense interest within the multiracial American Left. In this groundbreaking work, Teishan Latner contends that as Americans studied Cuba's achievements, Havana in turn looked to the US Left as a collaborator in the global battle against inequality and imperialism.